2011
DOI: 10.1111/j.1475-3588.2011.00629.x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot project of school‐based intervention integrating drama and language awareness

Abstract: Background: To help immigrant and refugee adolescents experiencing a severe academic delay cope with adversity, a school-based intervention combining drama workshops and language awareness activities was piloted in two classrooms. Method: A qualitative analysis of participant observations was performed and the Strength and Difficulty Questionnaire and its Impairment Supplement was administered before and after the intervention. The observations were carried out in two Montreal high schools serving an underpriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 14 publications
(16 reference statements)
2
64
0
Order By: Relevance
“…The three studies found no significant decreases in S‐ and T‐SDQ TDSs (viewed as secondary global measures by Rousseau et al, ). However, S‐SDQ impact or impairment ratings (viewed as primary outcomes) decreased significantly for Rousseau et al () and Rousseau et al (), and for first‐generation but not second‐generation youth (Rousseau et al, ). Control groups' S‐SDQ impact and T‐SDQ TDSs increased significantly (Rousseau et al, ; Rousseau et al, ), again possibly due to non‐intervention.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The three studies found no significant decreases in S‐ and T‐SDQ TDSs (viewed as secondary global measures by Rousseau et al, ). However, S‐SDQ impact or impairment ratings (viewed as primary outcomes) decreased significantly for Rousseau et al () and Rousseau et al (), and for first‐generation but not second‐generation youth (Rousseau et al, ). Control groups' S‐SDQ impact and T‐SDQ TDSs increased significantly (Rousseau et al, ; Rousseau et al, ), again possibly due to non‐intervention.…”
Section: Resultsmentioning
confidence: 90%
“…Three studies evaluated classroom‐based drama therapy workshops for refugee and immigrant youth in Canada (Rousseau, Armand, Laurin‐Lamothe, Gauthier, & Saboundjian, ; Rousseau et al, ; Rousseau et al, ). Students completed S‐SDQs in French, English, or students' (unspecified) native languages, supported by multilingual project staff (Rousseau et al, ); with interviewers (Rousseau et al, ); or requested translated versions (Rousseau et al, ). The three studies found no significant decreases in S‐ and T‐SDQ TDSs (viewed as secondary global measures by Rousseau et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first evaluated a 9-week school drama therapy program 26 and the second evaluated an intervention involving a 12-week series of workshops integrating drama and language awareness. 29 Both of these studies reported post-program/intervention reductions in impairment related to emotional and behavioural symptoms among participants compared with comparison groups. For the 9-week drama therapy program, performance in mathematics increased significantly compared with the comparison group, although there was no reported improvement in self-esteem or emotional and behavioural symptoms.…”
Section: Summary Of Study Findingsmentioning
confidence: 99%
“…The theatre workshops had previously been studied with classes of very recently arrived immigrants and refugees, which included youth with some learning, behaviour and emotional difficulties [22]. A pilot study also showed promising effects for classes of newcomers who presented a significant academic delay [23]. In both of these studies the youth were experiencing a rapid transition in culture and environment and the theatre workshops appeared to help them regain a sense of mastery and work through their past traumas and losses.…”
Section: Discussionmentioning
confidence: 99%